Transcutaneous Electrical Stimulation and Postoperative Total Knee Arthroplasty Pain - Mohamed N Mahomed; Gianni L Maistrelli; Ayoob Mossanen; Derek Glazier (Pain Research and Management)
OBJECTIVE: To determine the efficacy of the Synaptic 2000 in reducing total knee replacement postoperative pain in a prospective randomized controlled trial.